Acute Bilateral Limb Ischemia in Peripartum Cardiomyopathy: An Often Overlooked Complication - Muthia Syarifa Yani; Hary Sakti Muliawan (Jurnal Kardiologi Indonesia, 2026)
Background: Peripartum Cardiomyopathy is a specific subset of systolic heart failure with potentially devastating complications. Thromboembolism, as one of the complications, requires a careful evaluation to assess risk and guide management. This case report of acute limb ischemia complicating peripartum cardiomyopathy is an example of how to deal with thromboembolism in PPCM. Case Illustration: A 42-year-old woman came to our center with a classic presentation of acute heart failure; dyspnea on effort, paroxysmal nocturnal dyspnea, and orthopnea. These complaints started 4 months ago, just three weeks after her second childbirth. She had not taken medications diligently. Rales were heard on both lungs, with elevated jugular pressure and pitting edema on the extremities. Echocardiography revealed a dilated heart and reduced LVEF of 23%. She was diagnosed with PPCM and treated accordingly. On the first night in hospital, she felt sudden pain and paresthesia in her right foot. Distal pulse was weakly palpated, and there was hypoesthesia in the toes. Duplex ultrasound found fresh thrombi in bilateral popliteal arteries. Diagnosis of acute limb ischemia was confirmed, warranting the use of anticoagulants aside from her existing heart failure medications. Symptoms continued to improve until discharge. Conclusion: A case of a 42-year-old pregnant woman diagnosed with PPCM suffering from an acute thromboembolic episode was reported. Risk assessment is essential to predict the occurrence of future thromboembolism and therefore take necessary prevention before they happen. Different anticoagulants are indicated for different PPCM patient profiles, and careful consideration regarding their safety profile for this particular population is needed.